2009
DOI: 10.1002/art.24585
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunogenetic prognostic factors for radiographic severity in ankylosing spondylitis

Abstract: Objective. To improve prognostic ability in ankylosing spondylitis (AS), we sought to identify demographic, clinical, and immunogenetic characteristics associated with radiographic severity in a large cohort of patients. Methods. Patients with AS for >20 years were enrolled in a cross-sectional study (n ‫؍‬ 398). Pelvic and spinal radiographs were scored using the Bath Ankylosing Spondylitis Radiology Index for the spine (BASRI-s), and radiographic severity was measured as the BASRI-s/duration of AS. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 23 publications
(32 reference statements)
7
49
1
6
Order By: Relevance
“…[7,[13][14][15][16][17] However, the relationship between smoking and radiographic severity has not been consistent in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15]18] To our knowledge, the first survey which exposed the connection between smoking and AS patient outcomes was by Averns et al [15] in 1996. This investigation was included AS patients with a median duration of 20 years, and the authors found significant differences between smokers and non-smokers with regard to the finger-floor distance, Schober's test, total spinal involvement, occiput-to-wall distance, functional status, stiffness, and spinal radiographic damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7,[13][14][15][16][17] However, the relationship between smoking and radiographic severity has not been consistent in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15]18] To our knowledge, the first survey which exposed the connection between smoking and AS patient outcomes was by Averns et al [15] in 1996. This investigation was included AS patients with a median duration of 20 years, and the authors found significant differences between smokers and non-smokers with regard to the finger-floor distance, Schober's test, total spinal involvement, occiput-to-wall distance, functional status, stiffness, and spinal radiographic damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ward et al [3] revealed that radiographic severity is predicted by a history of smoking as well as age at disease onset, male gender, and some HLA alleles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients examined for this study were part of a large cohort enrolled at fi ve institutions to characterize the genetic risk for susceptibility and severity of AS. Patients were recruited from the clinics of the investigators, local rheumatologists, from patient support and advocacy groups, and from the community by advertisements (2)(3)(4). Enrollment occurred between February 2002 and January 2009.…”
Section: Study Subjectsmentioning
confidence: 99%